Nesting of Pachyramphus cf. polychopterus (Passeriformes: Tityridae) associated with Polybia fastidiosuscula de Saussure, 1854 (Hymenoptera: Vespidae) in an anthropized area of Atlantic Forest, southeastern Brazil - de Souza, Marcos Magalhães; de Moura, Aloysio Souza; de Sousa Oliveira, Glauco Cássio (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2024)
The nesting of birds associated with social wasps is well reported among different species, but there are few records of this interaction for the species Pachyramphus polychopterus (Tityridae). Therefore, the aim of our study was to report on the nesting of Pachyramphus cf. polychopterus with the social wasp Polybia fastidiosuscula de Saussure, 1854, in southeastern Brazil. According to previous studies and considering the distribution of both species, it is likely that the nesting of this bird associated with social wasp colonies is not occasional and isolated. However, further studies are still needed for a better understanding of the promoting and regulating factors, as well as to measure the supposed protection offered by the vespid wasps.
Keywords: Polistinae; Ethology; Social wasp